Talking Stick Learning Model Assisted with Audio Visual Media Toward Science Knowledge Competence - Phalguna, I Wayan Windu; Semara Putra, DB. Kt. Ngr (Universitas Pendidikan Ganesha, 2020)
The low competence of students' science knowledge is caused by the lack of optimal use of innovative and creative learning models and the lack of use of instructional media. The purpose of this research is to find out the significant influence of the talking stick model assisted by audio visual media on the science knowledge competence of fourth-grade elementary school students. The type of this study was quasi-experimental research with the non-equivalent control group design. The samples in this study were determined using the Cluster Random Sampling. The population in this study is all students in grade IV elementary school are 160 students. The data of science knowledge competence were collected using the test method and the instrument used was an ordinary multiple-choice objective. The data were analyzed using t-test. Based on the result of data analysis, the value of tcount=4,377 while at the significant level 5% and dk = 64 ttable=1,997 so that tcount=4,377 > ttable = 1,997. Based on the testing criteria, then Ho was rejected and ð»ð‘Ž was accepted. There were significant differences of the science knowledge competence between the group experimental and the control group. The average ofÂ science knowledge competence students in the experimental group and control group was 0,56 > 0,35. It can be concluded that the Talking Stick model assisted by audio visual media influence the science knowledge competence in the fourth-grade students of elementary school.